2015
DOI: 10.1007/s00425-015-2409-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative homologs of Larix decidua to BABYBOOM (BBM), LEAFY COTYLEDON1 (LEC1), WUSCHEL-related HOMEOBOX2 (WOX2) and SOMATIC EMBRYOGENESIS RECEPTOR-like KINASE (SERK) during somatic embryogenesis

Abstract: Embryogenesis-related genes ( LdBBM, LdLEC1, LdWOX2 and LdSERK ) were confirmed in sequence and expression abundance for Larix decidua —these findings are valid for somatic as well as for zygotic embryo development.S omatic embryogenesis is a reliable source of high-quality genotypes as it presents an advantageous alternative for conifers in forestry, independent from seed production. Although this propagation method is already being applied, molecular factors initiating and controlling the process remain to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 56 publications
6
46
3
Order By: Relevance
“…5a). CmSERK expression reached a peak in EC stage and then decreased gradually, while increased expression of LdSERK in Larix decidua was observed (Rupps et al 2016). The expression levels of CmSERK were detected in embryogenic and non-embryogenic calli, which was similar to the results reported for L. decidua, Secale cereale, as well as Medicago truncatula (Nolan et al 2003;Gurszczyńska and;Rakoczy-Trojanowska 2011;Rupps et al 2016).…”
Section: Expression Of Embryogenesis-related Genes During Somatic Embsupporting
confidence: 80%
See 3 more Smart Citations
“…5a). CmSERK expression reached a peak in EC stage and then decreased gradually, while increased expression of LdSERK in Larix decidua was observed (Rupps et al 2016). The expression levels of CmSERK were detected in embryogenic and non-embryogenic calli, which was similar to the results reported for L. decidua, Secale cereale, as well as Medicago truncatula (Nolan et al 2003;Gurszczyńska and;Rakoczy-Trojanowska 2011;Rupps et al 2016).…”
Section: Expression Of Embryogenesis-related Genes During Somatic Embsupporting
confidence: 80%
“…CmSERK expression reached a peak in EC stage and then decreased gradually, while increased expression of LdSERK in Larix decidua was observed (Rupps et al 2016). The expression levels of CmSERK were detected in embryogenic and non-embryogenic calli, which was similar to the results reported for L. decidua, Secale cereale, as well as Medicago truncatula (Nolan et al 2003;Gurszczyńska and;Rakoczy-Trojanowska 2011;Rupps et al 2016). As a specific marker of embryogenic cells (Schmidt et al 1997), combined with a high expression level at an early stage of this study, we propose that CmSERK plays a crucial role in the initiation of embryogenesis in Chinese chestnut.…”
Section: Expression Of Embryogenesis-related Genes During Somatic Embmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes play important roles in various developmental events, such as zygote polarization, embryonic tissue proliferation, embryonic pattern formation, stem cell niche maintenance and flower development and lateral organ development (Breuninger et al 2008;Chung et al 2016;Costanzo et al 2014;Ueda and Laux 2012;Wu et al 2007;Zhou et al 2015). The WOX gene family is evolutionarily conserved throughout the plant kingdom (van der Graaff et al 2009), and their orthologs also showed specific expression in zygotic and/or somatic embryogenesis in different species; for example, Vitis vinifera (Gambino et al 2011), Populus tomentosa (Liu et al 2014) and the gymnosperms Larix decidua (Rupps et al 2016) and Picea abies (Hedman et al 2013;Palovaara et al 2010;Zhu et al 2016), suggesting their functional conservation.…”
Section: Introductionmentioning
confidence: 99%